Pengaturan Hukum Internasional Untuk Tenaga Kerja Anak Ilegal - Latukaisupy, Norma Rizqitha; Anwar, Arman; Daties, Dyah Ridhul Airin (Faculty of Law, Universitas Pattimura, 2021)
Introductioan: The purpose of this study is to explain the problem of child labor in general that requires deeper attention, with the consideration that employing a child who is still below the minimum human limit for work can be interpreted as a form of human rights violation.Purposes of the Research: Know and analyze the regulations regarding international law for illegal child labor.Methods of the Research: This study uses a normative juridical method with legal materials used in the study are primary, secondary and tertiary with the use of literature study techniques in the form of international legal regulations, scientific papers and literature.Results of the Research: The results showed that child labor was found in exploited conditions, worked more than the time stated in the regulations and received wages far below the UMK. Child laborers also have not received protection in terms of legal aspects that has been ratificated by the national law. The existing legal protection system for child labor has not been implemented in real terms and the Convention on the Rights of the Child and the ILO Conventions as some of the protection systems for child labor cannot be fully implemented because there are still violations of the right for children.